Maskless atmospheric pressure PECVD of SiOx films on both planar and nonplanar surfaces using a flexible atmospheric microplasma generation device. Issue 1 (23rd October 2019) - Wang, Tao; Liu, Jingquan; Shi, Liping; Zhang, Xingquan; Lv, Li; Zhang, Guotao; Wang, Jun
Abstract: This paper presents the use of a simple‐arranged, low‐cost, and flexible atmospheric pressure microplasma generation device (μPGD) with controlled gas discharge to achieve maskless atmospheric plasma‐enhanced chemical vapor deposition (PECVD) of SiO x films on both planar and nonplanar surfaces. The μPGD is mainly composed of a copper–polyimide–copper sandwich structure with predefined microfluidic channels. Uniform microplasmas of different shapes and dimensions were generated in the open air. SiO x films were masklessly deposited with well‐defined edges and good feature transfer fidelity. The SEM, EDS, XPS, and FTIR spectra of the deposited film confirm the SiO x structure. These results indicate that μPGD is able to achieve maskless PECVD of SiO x films in the open air, especially micropatterning on nonplanar surfaces. Abstract : This paper presents the use of a simple‐arranged, low‐cost, and flexible atmospheric pressure microplasma generation device with controlled gas discharge to achieve maskless atmospheric pressure plasma‐enhanced chemical vapor deposition of SiO x films on both planar and nonplanar surfaces.